Improvement of Life Skills through Handwashing Habit (Action Research on Children of Group A in Kindergarten Al-Fidaa Bekasi, Indonesia) - Edy Mustofa; Khausar Khausar (BIRCU, 2019)
Life Skills is an ability possessed by someone to behave positively, self-regulate, and socially skilled. Handwashing habit is an activity carried out in an action or behavior that trains children to have proper handwashing skills. This study aims to determine the improvement of life skills through the habit of washing hands. This type of research is action research. The subjects in this study were the children of Group A Al-Fidaa Kindergarten (TK), Tambun Selatan District, Bekasi Regency, Indonesia, totaling 10 children. This study consisted of 2 cycles, each cycle carried out as many as 8 meetings. The results showed that through the habit of washing hands can improve children's life skills. The results of the study of children's life skills in pre-cycle that is equal to 40% and increased in the first cycle to 65% then increased to 89% in the second cycle with a very well developed category.